Сoncept of special pre-trial investigation (in absentia) and its functionality in criminal proceedings on corruption crimes in field of official activity and professional activities related to the provision of public services - Шевчишен , А. В. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2017)
The article is based on an analysis of the current criminal procedure law, its application and special literature defines the concept of special pre-trial investigation and its functionality in criminal proceedings on corruption crimes in field of official activity and professional activities related to the provision of public services, proposed changes to the current Code of Ukraine, aimed at optimizing the normative legal regulation implementation and termination of special pre-trial investigation. In particular, it is proposed to define a special pre-trial investigation – is an extraordinary exercise of the pre-trial investigation, which is used in criminal procedural law provided evasion suspect from criminal responsibility by hiding from the investigation and trial, aims to provide evidence under preliminary investigation in the criminal proceedings with the standards of fair justice. Established that the functionality of the special pre-trial investigation is to provide prompt, full and impartial investigation and subsequent trial by gathering evidence in criminal proceedings in terms of counteracting the investigation of the suspect in the form of evasion of the suspect from criminal responsibility by hiding from the investigation and of the court and ensure the right of a suspect to defense through the implementation of its procedural rights during pre-trial investigation by the defender. Criminal procedural law proposed to supplement the rules, which provide for duty investigating judge in ruling on the implementation of the special pre-trial investigation noted that this decision shall be terminated in cases of arrest authorized officer a suspect who was declared wanted, or voluntary appearance before pre-trial investigation and the prosecutor supervising the procedural guidance in the form of pre-trial investigation, to bring information to the Unified Register of pre-trial investigation to terminate criminal proceedings in a special pre-trial investigation.

У статті на підставі аналізу чинного кримінального процесуального законодавства, практики його застосування і спеціальної літератури визначено поняття спеціального досудового розслідування та його функціональне призначення у кримінальних провадженнях щодо корупційних злочинів у сфері службової діяльності та професійної діяльності, пов’язаної з наданням публічних послуг, запропоновано зміни до чинного КПК України, які спрямовані на оптимізацію нормативно-правової регламентації здійснення та припинення спеціального досудового розслідування.
ПОНЯТТЯ СПЕЦІАЛЬНОГО ДОСУДОВОГО РОЗСЛІДУВАННЯ (IN ABSENTIA) ТА ЙОГО ФУНКЦІОНАЛЬНЕ ПРИЗНАЧЕННЯ У КРИМІНАЛЬНИХ ПРОВАДЖЕННЯХ ЩОДО КОРУПЦІЙНИХ ЗЛОЧИНІВ У СФЕРІ СЛУЖБОВОЇ ДІЯЛЬНОСТІ ТА ПРОФЕСІЙНОЇ ДІЯЛЬНОСТІ, ПОВ’ЯЗАНОЇ З НАДАННЯМ ПУБЛІЧНИХ ПОСЛУГ
Keywords: pre-trial investigation; special pre-trial investigation; suspect; wanted ads; international search.; досудове розслідування; спеціальне досудове розслідування; підозрюваний; оголошення у розшук; міжнародний розшук.